Analysis services administration staffing agencies offices in the areas of Majene - Burhanuddin Burhanuddin (Indonesia Prime, 2017)
Standard service will need to have a clear benchmark that can use as a reference for action on every State Government organizers. Good service is how to implement the legislation as efficiently as possible, scientifically, and politically neutral. Checkout process administration promoted generally give answers that the apparatus is in running its job quite well, but in settlement of any administration is not clear. one of the factors affecting the obscurity that, because Agencies Staffing offices do not yet have an operational service standard in providing service.